Viabilidade financeira da implantação do projeto de construção da estação de tratamento de esgotos - ETE - do Município de Lençóis Paulista - Estado de São Paulo - Toledo, Julio Cesar Scaramuzzi de [UNESP] (2008)
This dissertation has the purpose to present and compare quantitative data about waste treatment station, placed in Lençóis Paulista city, in the state of Sao Paulo. At first, this work had the intent to present financial and environmental data, however, the project not in operation, it showed only financial data. These data demonstrate the amount of money invested, as also, the revenues and expenses inherent of operation. This work used the traditional investment analysis method, like net present value, interested rate return and payback. To calculate the project risk probability, it was used normal distribution. The waste water collected is fundamental to guarantee the population's life quality. However, one of the major reason to quality's water degradation is the pollution resulted of throwing waste waters in creeks, rivers and others flow waters which justify the need to treat them, reducing the amount of pollution before their final disposal. According to Brazilian's Government statistics, only 20,2% of waste water from brazilian's homes receives proper treatment, and just a small quantity is returned in sanitary way to the environment. (IBGE, 2003). In such a way, this study esposes a contemporary problem, demonstrating quantitatively, that the implementation of ETE is financially viable, like demonstrated calculation of the net present value (NPV), internal interested rate (IRR), and payback. That investments methods evaluation was sensibility through an probability series about population growth, that make possible calculated the project risk, wich result confirm the viability of the project.